2003
DOI: 10.1074/jbc.m212056200
|View full text |Cite
|
Sign up to set email alerts
|

A Two-drug Model for Etoposide Action against Human Topoisomerase IIα

Abstract: The widely used anticancer drug etoposide kills cells by increasing levels of topoisomerase II-mediated DNA breaks. While it is known that the drug acts by inhibiting the ability of topoisomerase II to ligate cleaved DNA molecules, the precise mechanism by which it accomplishes this action is not well understood. Because there are two scissile bonds per enzyme-mediated doublestranded DNA break, it has been assumed that there are two sites for etoposide in every cleavage complex. However, it is not known whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
140
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(151 citation statements)
references
References 56 publications
6
140
2
Order By: Relevance
“…Etoposide occupancy at both scissile bonds is required for DSBs, and most breaks formed at concentrations relevant to chemotherapy are SSNs (Bromberg et al 2003). Consistent with reports in which the vast majority of detected TOP2 cleavage events were SSNs (Bromberg et al 2003;Muslimovic et al 2009), we found 1.3%-3.4% of TOP2A cleavage events were DSBs and the remainder were SSNs (Supplemental Table S1; Supplemental Fig.…”
Section: Top2a Cleavage Events Are Ssns More Often Than Dsbssupporting
confidence: 77%
“…Etoposide occupancy at both scissile bonds is required for DSBs, and most breaks formed at concentrations relevant to chemotherapy are SSNs (Bromberg et al 2003). Consistent with reports in which the vast majority of detected TOP2 cleavage events were SSNs (Bromberg et al 2003;Muslimovic et al 2009), we found 1.3%-3.4% of TOP2A cleavage events were DSBs and the remainder were SSNs (Supplemental Table S1; Supplemental Fig.…”
Section: Top2a Cleavage Events Are Ssns More Often Than Dsbssupporting
confidence: 77%
“…A possible explanation for this additive effect is the different mechanisms of action against topo II conferred by the two drugs. Bromberg et al (2003b) have shown that VP-16 acts by inhibiting the ability of topo II to ligate cleaved DNA molecules, whereas quinolones have little effect on ligation but stimulate the forward rate of topo II-mediated DNA cleavage. These two distinct mechanisms may work in concert and lead to the observed additivity in the antiproliferative effects of VP-16 and MXF.…”
Section: Discussionmentioning
confidence: 99%
“…rical Top2cc in which only one DNA strand is cleaved at any given time (8,32,33). Therefore, the tyrosine from a trapped topoisomerase can be linked to different types of DNA ends.…”
Section: Ribonucleotide Incorporation Enhances Irreversible Top2cc Bumentioning
confidence: 99%